2020
DOI: 10.1021/acsami.9b20952
|View full text |Cite
|
Sign up to set email alerts
|

Selective Growth of Stacking Fault Free ⟨100⟩ Nanowires on a Polycrystalline Substrate for Energy Conversion Application

Abstract: Cubic semiconductor nanowires grown along ⟨100⟩ directions have been reported to be promising for optoelectronics and energy conversion applications, owing to their pure zinc-blende structure without any stacking fault. But, until date, only limited success has been achieved in growing ⟨100⟩ oriented nanowires. Here we report the selective growth of stacking fault free ⟨100⟩ nanowires on a commercial transparent conductive polycrystalline fluorine-doped SnO2 (FTO) glass substrate via a simple and cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In group II-VI and III-V binary semiconductor NW systems, due to the crystal polarity of the material and the combination of low energy and high symmetry of the [111] direction, the ZnSe NWs tend to grow in a zincblende cubic structure along the [111] direction 56 . However, in recent years, non-[111]-oriented semiconductor NWs have attracted increasing interest in terms of fundamental research and promising applications due to their outstanding crystal quality and distinctive physical properties [57][58][59] . Introducing numerous growth techniques, (1) Firstly, we investigate the significance of crystal orientation on the stress-strain response behavior of the zinc-blende ZnSe NWs.…”
Section: Resultsmentioning
confidence: 99%
“…In group II-VI and III-V binary semiconductor NW systems, due to the crystal polarity of the material and the combination of low energy and high symmetry of the [111] direction, the ZnSe NWs tend to grow in a zincblende cubic structure along the [111] direction 56 . However, in recent years, non-[111]-oriented semiconductor NWs have attracted increasing interest in terms of fundamental research and promising applications due to their outstanding crystal quality and distinctive physical properties [57][58][59] . Introducing numerous growth techniques, (1) Firstly, we investigate the significance of crystal orientation on the stress-strain response behavior of the zinc-blende ZnSe NWs.…”
Section: Resultsmentioning
confidence: 99%
“…15,19,51 However, because of their excellent crystal superiority and unique physical features, other orientational semiconductor NWs have gained growing interest in basic research and prospective applications. 52–54 The selective growth of stacking fault-free ZnTe NWs along [100], [110], and [112] crystal orientations is reported using a variety of growth processes, including molecular beam epitaxy and the vapor–liquid–solid growth processes. 55,56 Prior studies also revealed that by maintaining cross-linking among the NWs length, diameter, and growth conditions, NWs can be grown along any of these [110], [100], [112], or [111] four orientations, which are confirmed by X-ray diffraction, photoluminescence spectroscopy, and transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] synthesized an N‐doped TiO 2 photoanode and demonstrated the superior ability in extending the absorption spectrum and enlarging the specific surface area, which then presented remarkable efficacy in promoting the redox couples conversion and intensifying the solar energy storage. Meanwhile, considering the noteworthy roles of materials structure in influencing both charge carriers transport and mass transfer as well as the quantity of active sites, [ 5a,48 ] which may be the essential conditions to satisfy the extremely fast kinetics of redox reactions, [ 49 ] various structures of the photoelectrode materials have also been proposed. [ 50 ] A typical structure is nanotube, where the larger active surface area and more porous structure can intensify the proton and mass transport and avail the light scattering to deplete the photons, and the sufficient grain boundary plays a favorable role in promoting electron transfer.…”
Section: Energy Level Matching Between Redox Couples and Photoelectrodesmentioning
confidence: 99%